TRAINING OF DIFFICULT MATERIALS AND DESIGNING HOTS BASED QUESTIONS AT MGMP BIOLOGY OF SMA ACEH BARAT REGENCY - Hasanuddin, Hasanuddin; Nurmaliah, Cut; Artika, Wiwit (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2022)
The purpose of this Community Service activity is to provide a training in the preparation of questions in the category of the Higher Order Thinking Skills (HOTS). The specific target to be achieved from this activity is the high school teachers that join in the Biology MGMP group of Aceh Barat District are able to compile HOTs questions category which have been considered difficult. The implementation of these activity is carried out for Biology teachers who are joining in the Group of Biology Subject Teachers Conference (MGMP) at high school level. The MGMP was chosen because it is a form of activity forum in order to address the lack of mastery in preparing HOTS-based questions. MGMP is not only a deliberation institution, but can be used as a scientific forum for the teachers and resource person and also as a peer supervision institution. The target for 2021 activities proposed through this proposal is held for Biology MGMP at Aceh Barat District high school. Mentoring materials are limited to the preparation of HOTS questions. Keywords: Difficult materials, Hots, Aceh Barat